2017
DOI: 10.1017/s0033291717000642
|View full text |Cite
|
Sign up to set email alerts
|

Brain volume changes over the first year of treatment in schizophrenia: relationships to antipsychotic treatment

Abstract: Brain volume reductions associated with antipsychotic treatment are not restricted to poor outcome patients and occur even with the lowest effective dose of antipsychotic. The lack of an association with poor treatment response or treatment-related adverse effects counts against cortical volume reductions reflecting neurotoxicity, at least in the short term. On the other hand, the volume reductions were not linked to the therapeutic benefits of antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Numerous studies have found that changes in brain imaging occurred at an early stage in schizophrenia, while structural and functional abnormalities in brain regions caused by grey and white matter volume reductions and anomalous connections, became more prominent with the progression of the condition. But Emsley et al argued that the brain volume reductions are not directly associated with antipsychotic treatment during the first year of medication, and decrease in brain volume may have more to do with neurotoxicity of drugs than with the therapeutic effect (64). However, due to the differences in research facilities and measuring methods, conclusions are still controversial because abnormal brain regions in various studies do not completely overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that changes in brain imaging occurred at an early stage in schizophrenia, while structural and functional abnormalities in brain regions caused by grey and white matter volume reductions and anomalous connections, became more prominent with the progression of the condition. But Emsley et al argued that the brain volume reductions are not directly associated with antipsychotic treatment during the first year of medication, and decrease in brain volume may have more to do with neurotoxicity of drugs than with the therapeutic effect (64). However, due to the differences in research facilities and measuring methods, conclusions are still controversial because abnormal brain regions in various studies do not completely overlap.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis revealed greater cortical gray matter decrease with higher daily antipsychotic intake in patients treated with first‐generation antipsychotic drugs ( Z , –2.31, P = 0.02) and less cortical gray matter decrease with higher daily antipsychotic intake in patients treated with second‐generation antipsychotics ( Z , 0.78, P = 0.439); the doses were calculated by chlorpromazine equivalent ranging from 160 to 415 mg/day . Other studies have shown that antipsychotic drugs induced a trend of cortical gray matter volume reduction ( P = 0.052); however, no differences were found in cortical gray matters between the first and second generations of antipsychotic drug treatment including haloperidol (3–9 mg/day), risperidone (3–6 mg/day), and olanzapine (5–20 mg/day) after a 1‐year trial; these were considered to be relatively low doses of treatment . An animal study has shown that macaque monkeys treated with haloperidol and olanzapine for 17–27 months showed a decrease in brain weight of 8–11% and these reductions were across a number of brain areas including the frontal, temporal, parietal, and cerebellum .…”
Section: The Effects Of Antipsychotic Drugs On Neuritesmentioning
confidence: 98%
“…A voxel-wise volume study on first-episode drug-naive patients with schizophrenia found a significant GMV increase in the right putamen after 6 weeks of antipsychotic treatment, and this increase was associated with an improvement in positive symptoms [ 18 ]. However, in a very recent study, although cortical volume reductions occurred in drug-naive patients during their first year of treatment, they showed no significant association with changes in the symptoms, treatment-related side-effects, age, gender, and duration of untreated psychosis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%